The Affecting Factors on Computer Based Test of National English Examination at SMAN 1 Raha - Nusi, Amelia Amanda; Nggawu, La Ode; Fatmawati, Wa Ode (Journal of Teaching of English, 2021)
This study was conducted to investigate the factors that affect English national examination success in Computer Based Test (CBT) at SMAN 1 Raha. This study's research question was "What are factors that affect the success of English national examination in Computer Based Test (CBT) at SMAN 1 Raha?". The study's objective is to find out information about the factors that affect national English examination success in Computer Based Test (CBT) at SMAN 1 Raha. This study used a descriptive design. The types of data in this study were (a) primary data, directly collected from interviews with teachers at SMAN 1 Raha (teacher interview), and (2) secondary data was collected by observation and documentation to support the primary data (observation and documentation). The study subjects were three teachers of SMAN 1 Raha who were being involved in the examination committee. The collected data were analyzed through the following steps: (1) data reduction,Â  implemented by summarizing field notes, sorting out the main things related to the test succession factors, and compiling them systematically in order to provide a sharper picture and make it easier to track back when the data is needed. (2) Data display, to see the overall picture of the study results, the researcher displays the collected data to map factors that are affecting the test succession. (3) Conclusions and verification, to picture out how the factors affect the test succession, the researcher draws the following conclusions; (1) The success of the National Computer Based Test (CBT) implementation is highly influenced by facility availability based on national computer-based test standards that consist of human resources, internet networks, servers, and electricity. (2) SMAN 1 Raha conducted the National Computer Based Test (CBT) successfully in the academic year 2017/2018 for the first time.